Enhanced antitumor activity of surface-modified iron oxide nanoparticles and an α-tocopherol derivative in a rat model of mammary gland carcinosarcoma - Horák D; Pustovyy VI; Babinskyi AV; Palyvoda OM; Chekhun VF; Todor IN; Kuzmenko OI (International Journal of Nanomedicine, 2017)
Daniel Horák,1 Vitaliy Igorovych Pustovyy,2 Andrii Valeriyovich Babinskyi,2 Olga Mikhailovna Palyvoda,2 Vasyl Fedorovich Chekhun,3 Igor Nikolaevich Todor,3 Oleksandr Ivanovich Kuzmenko2 1Department of Polymer Particles, Institute of Macromolecular Chemistry AS CR, Prague, Czech Republic; 2Department of Vitamins and Coenzyme Biochemistry, Palladin Institute of Biochemistry, NASU, Ukraine; 3Department of Mechanisms of Antitumor Therapy, R. E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, NASU, Ukraine Abstract: Maghemite (γ-Fe2O3) nanoparticles were obtained by coprecipitation of ferrous and ferric salts in an alkaline medium followed by oxidation; the nanoparticles were coated with poly(N,N-dimethylacrylamide) (PDMA) and characterized by transmission electron microscopy, attenuated total reflection (ATR) Fourier transform infrared (FTIR) spectroscopy, dynamic light scattering, thermogravimetric and elemental analyses, and magnetic measurements in terms of particle morphology, size, polydispersity, amount of coating, and magnetization, respectively. The effects of α-tocopherol (Toc) and its phenolic (Toc-6-OH) and acetate (Toc-6-Ac) derivatives on Fe2+ release from γ-Fe2O3@PDMA, as well as from γ-Fe2O3 and CuFe2O4 nanoparticles (controls), were examined in vitro using 1,10-phenanthroline. The presence of tocopherols enhanced spontaneous Fe2+ release from nanoparticles, with Toc-6-OH exhibiting more activity than neat Toc. All of the nanoparticles tested were found to initiate blood lipid oxidation in a concentration-dependent manner, as determined by analysis of 2-thiobarbituric acid reactive species. Wistar rats with Walker-256 carcinosarcoma (a model of mammary gland carcinosarcoma) received Toc-6-Ac, magnetic nanoparticles, or their combination per os, and the antitumor activity of each treatment was determined in vivo. γ-Fe2O3@PDMA nanoparticles exhibited increased antitumor activity compared to both commercial CuFe2O4 particles and the antitumor drug doxorubicin. Moreover, increased antitumor activity was observed after combined administration of γ-Fe2O3@PDMA nanoparticles and Toc-6-Ac; however, levels of bilirubin, aspartate aminotransferase, and white bloods normalized and did not differ from those of the intact controls. The antitumor activity of the γ-Fe2O3 nanoparticles strongly correlated with Fe2+ release from the nanoparticles but not with nanoparticle-initiated lipid peroxidation in vitro. Keywords: iron oxide nanoparticles, poly(N,N-dimethylacrylamide), lipid oxidation, oxidative stress, antitumor activity, α-tocopherol